Describing Self-efficacy of In-experienced English Teachers in Elementary Schools - Ramadani, Putri Aulia; Fajaria, Nurul Hasanah; Zarkasih, Enci (Universitas Muhammadiyah Mataram, 2025)
This study aims to describe the self-efficacy level of inexperienced English teachers in elementary schools. This study used a descriptive quantitative approach with a questionnaire instrument based on the Teachers' Sense of Efficacy Scale (TSES) theory which includes three main domains: student engagement, instructional strategies, and classroom management. The research subjects consisted of 35 elementary school teachers who taught English but did not have an English education background. The results showed that teachers' self-efficacy levels were generally high, with the classroom management domain receiving the highest score with score (30.9), followed by instructional strategies with score (30.8), and the lowest score on student engagement with score (29.6). This finding indicates that although teachers have no specific experience in teaching English, they have good self-efficacy in managing the classroom and designing lessons. Although research on teacher self-efficacy has been widely conducted in various educational contexts, not much is known about the self-efficacy of novice English teachers in primary schools in Indonesia, especially those who do not have an English language education background or teaching certification. This study addresses the gap of elementary school teachers who do not have an English education background However, they still face challenges in motivating and actively engaging students. This study recommends the need for specialized training that focuses on developing interactive strategies to improve student engagement in English language learning.